CYBERTHREATS, CYBERBULLYING, AND CYBERSTALKING: A CRITICAL EXAMINATION OF DIGITAL HARASSMENT IN THE CONTEMPORARY ERA - Qazi, Khursheed Ahmad; Hamid, Sumaira (ShodhKosh: Journal of Visual and Performing Arts, 2023)
With the rapid evolution of digital technologies, the internet and social media platforms have become integral to modern life. However, these advancements have also given rise to new forms of harassment, such as cyberthreats, cyberbullying, and cyberstalking. Each of these forms of online abuse can have far-reaching consequences on individuals, particularly regarding their mental health and safety. This paper critically examines the nature, psychological effects, and legal frameworks surrounding these forms of digital harassment. By analyzing specific real-world cases like the Bulli Bai and Sulli Deals apps, the paper emphasizes the urgency of tackling these problems through more robust legal measures, social awareness, and support systems for victims. The paper also explores preventive strategies that can be implemented by individuals, technology companies, and lawmakers to reduce the incidence of digital harassment and ensure safer online spaces.